2006
DOI: 10.1007/s00330-006-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dose from common head and neck CT examinations in children: is there an excess risk for thyroid cancer induction?

Abstract: This study was conducted to estimate thyroid dose and the associated risk for thyroid cancer induction from common head and neck computed tomography (CT) examinations during childhood. The Monte Carlo N-particle transport code was employed to simulate the routine CT scanning of the brain, paranasal sinuses, inner ear and neck performed on sequential and/or spiral modes. The mean thyroid dose was calculated using mathematical phantoms representing a newborn infant and children of 1year, 5 years, 10 years and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 14 publications
2
87
0
2
Order By: Relevance
“…The mean radiation dose to the thyroid from a CT scan of the neck ranges from 17-34 mGy, which is within the range that may increase the risk for thyroid cancer in children. [18][19][20] However, most people receiving neck CT scans are older adults, and the risk for cancer from radiation exposure decreases sharply with increasing age. 21 Pooled analyses of studies of thyroid cancer in patients exposed to radiation found that there was little risk for excess cancer when exposure was after age 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…The mean radiation dose to the thyroid from a CT scan of the neck ranges from 17-34 mGy, which is within the range that may increase the risk for thyroid cancer in children. [18][19][20] However, most people receiving neck CT scans are older adults, and the risk for cancer from radiation exposure decreases sharply with increasing age. 21 Pooled analyses of studies of thyroid cancer in patients exposed to radiation found that there was little risk for excess cancer when exposure was after age 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a typically younger patient population and the proximity of radiosensitive organs such as the eye lenses and thyroid gland, increased concern is focused on radiation dosage. 4,5 Given the relatively small diameter of the head in comparison with the trunk and the high intrinsic contrast of the evaluated structures, CT can be performed with adapted dose parametersdepending on the indication. 2,6 Reducing the tube current is eventually limited by increased noise leading to a decrease in image quality, however.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid gland exposure during a head and neck CT scan is up to 52.0 mGy (17). Neck CT scans are associated with an increased risk of developing thyroid cancer up to 390 per million patients (17). Chemical exposure should also be considered.…”
Section: Thyroid Cancer Epidemic 477mentioning
confidence: 99%